Individual and Organizational Factors that Affect Political Behavior - (:unkn) unknown (My University, 2007)
Politik davranış kurumsal olarak onaylanmayan ve kurumsal amaçlara ya da kurumda çalışanların çıkarlarına zarar verebilecek davranışlar olarak tanımlanmaktadır. Son dönemde yapılan araştırmalar politik davranışa neden olan çok sayıda faktörün olduğunu belirlemiştir. Bunlardan bazıları bireysel, bazıları da kurumsal niteliktedir. Bu çalışmada, politik davranışı etkileyen kurumsal ve bireysel faktörlerin ortaya çıkarılması amaçlanmaktadır. Çalışmada anket yöntemi kullanılmış ve farklı sektör ve kurumda çalışanlara anket dağıtılmıştır. Örneklem kolay ulaşılabilir örneklemedir. Toplam 350 anket dağıtılmıştır. Geri dönüşüm oranı %94'tür. Yapılan regresyon analizi sonucunda hem bireysel hem de kurumsal faktörlerin politik davranışı etkilediği ortaya çıkmıştır.

Political behavior is defined as organizationally non-sanctioned behavior which may be detrimental to organizational goals or to the interests of others in the organization. Recent research has identified a number of factors that encourage political behavior. Some of these factors are individual and some are organizational factors. This study aims to find out which of the organizational and individual factors affect political behavior. The study is conducted by distributing questionnaires to employees in different organizations and sectors. The sampling is convenience sampling. The sample includes 350 individuals. The response rate is 94%. The results of the regression analyses revealed that both individual and organizational factors affect political behavior.
Politik Davranışı Etkileyen Bireysel ve Kurumsal Faktörler
Keywords: İktisat; İşletme